Fandom Power: Examining Customer Engagement, Attitudes, and Purchase Intentions in K-Pop Fandom-Brand Collaborations - Tertiano, Raffi Fairuza; Salehudin, Imam (ASEAN Marketing Journal, 2023)
Manuscript type: Empirical paper Research Aims: This study examines the impact of the Korean Wave (Hallyu) fandom in Indonesia, focusing on collaborations between Indonesian companies and K-Pop idols. It aims to understand how fan interactions influence purchasing behavior toward celebrity-endorsed products. Design/methodology/approach: The research employs Structural Equation Modeling (SEM) to analyze data from 1,016 respondents familiar with collaboration campaigns between Indonesian companies and K-Pop idols. It examines customer-to-customer identification (CCI), customer-to-community identification (CMI), attitudinal engagement, behavioral engagement, attitude toward brand, and attitude toward celebrity. Research Findings: The findings reveal that CCI is positively linked to CMI and enhances customer attitudinal engagement. Furthermore, CMI significantly impacts both attitudinal and behavioral customer engagement. while attitude toward celebrity predicts purchase intention, attitude toward brand does not. These results highlight the complex dynamics within K-Pop fandoms and their influence on consumer behavior. Theoretical Contribution/Originality: This study contributes to the literature by providing a deeper understanding of distinct types of fan identification and their impacts on different forms of customer engagement. It underscores the importance of celebrity endorsements in shaping purchase intentions within the context of the Hallyu phenomenon. Practitioner/Policy Implication: The insights from this research can inform marketing strategies for companies leveraging the popularity of K-Pop idols. Marketers should focus on enhancing fan identification and engagement, particularly leveraging celebrity influence to drive purchase intentions. Research limitation/Implications: The study is limited to Indonesian fans and specific collaboration campaigns. Future research could expand to other countries and different celebrity endorsements to validate and extend the findings. Keywords: K-pop, fandom, social identification, customer engagement, purchase intention